Porcupine inhibitor CGX1321 alleviates heart failure with preserved ejection fraction in mice by blocking WNT signaling - Wu Hao; Tang Lu-xun; Wang Xue-mei; Li Liang-peng; Chen Xiao-kang; He Yan-ji; Yang De-zhong; Shi Yu; Shou Jia-ling; Zhang Zong-shu; Wang Liang; Lu Bing-jun; et al. (Acta Pharmacologica Sinica, 2023)
Heart failure with preserved ejection fraction (HFpEF) is highly prevalent, and lacks effective treatment. The aberration of WNT pathway underlies many pathological processes including cardiac fibrosis and hypertrophy, while porcupine is an acyltransferase essential for the secretion of WNT ligands. In this study we investigated the role of WNT signaling pathway in HFpEF as well as whether blocking WNT signaling by a novel porcupine inhibitor CGX1321 alleviated HFpEF. We established two experimental HFpEF mouse models, namely the UNX/DOCA model and high fat diet/L-NAME (“two-hit”) model. The UNX/DOCA and “two-hit” mice were treated with CGX1321 (3 mg·kg−1·d−1) for 4 and 10 weeks, respectively. We showed that CGX1321 treatment significantly alleviated cardiac hypertrophy and fibrosis, thereby improving cardiac diastolic function and exercise performance in both models. Furthermore, both canonical and non-canonical WNT signaling pathways were activated, and most WNT proteins, especially WNT3a and WNT5a, were upregulated during the development of HEpEF in mice. CGX1321 treatment inhibited the secretion of WNT ligands and repressed both canonical and non- canonical WNT pathways, evidenced by the reduced phosphorylation of c-Jun and the nuclear translocation of β-catenin and NFATc3. In an in vitro HFpEF model, MCM and ISO-treated cardiomyocytes, knockdown of porcupine by siRNA leads to a similar inhibitory effect on WNT pathways, cardiomyocyte hypertrophy and cardiac fibroblast activation as CGX1321 did, whereas supplementation of WNT3a and WNT5a reversed the anti-hypertrophy and anti-fibrosis effect of CGX1321. We conclude that WNT signaling activation plays an essential role in the pathogenesis of HFpEF, and porcupine inhibitor CGX1321 exerts a therapeutic effect on HFpEF in mice by attenuating cardiac hypertrophy, alleviating cardiac fibrosis and improving cardiac diastolic function.